Association between Vitamin D Deficiency and Asthma in childhood - Qurat-ul-Ain Aslam,Saima Akhtar,Muhammad Hafeez, Shahzadi Sumbal Ghazi,Samina Yaqoob,Uzma Abid , Qurat-ul-Ain Aslam,Saima Akhtar,Muhammad Hafeez, Shahzadi Sumbal Ghazi,Samina Yaqoob,Uzma Abid (Journal of Rawalpindi Medical College, 2019)
Background: This study was designed to determine relationship between vitamin D deficiency and asthma in pediatric age group as compared to controls. Asthma is among one of the major causes of morbidity in children and it is suggested that vitamin D deficiency plays a role in asthma severity since it has immunomodulatory effects. Methods: This case control study was performed at Benazir Bhutto Hospital Rawalpindi in pediatric department from 2014 to 2015. Cases and controls were recruited from the same hospital through consecutive sampling. Cases were patients with asthma and controls were patients with minor illness other than asthma presenting in outpatient department. The patients who had rickets, known vitamin D deficiency, renal disease, liver disease and other respiratory problems (tuberculosis, pneumonia cystic fibrosis) as assessed on medical records or history and examination were excluded both for cases and controls. Vitamin D levels were checked in all patients. The data was recorded and analysis was done through SPSS 14. Results: The two groups were comparable for age and gender. Mean age of patients in cases was7.66+2.92 while among controls it was 7.23± 2.65 years. Among 30 patients with asthma, vitamin D deficiency was found in 19 (63.33%) while in controls it was found in 8 patients (26.67%). P value was 0.004 which was statistically significant. odds ratio was 4.75, 95 % confidence interval for odds ration showing significant difference between two groups Conclusion: Vitamin D deficiency was remarkably higher in asthmatics in comparison to non-asthmatic children.